2008
DOI: 10.1007/s10980-008-9293-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant species response to urbanization: comparison of isolated woodland patches in two cities of North-Western France

Abstract: International audienceThe effect of urbanization on species distribution has been extensively documented, but a main challenge in urban ecology is to better understand the factors causing different distributions among species in response to urbanization. Hence, this paper aims to compare the effects of urbanization on woodland plant assemblages in two cities and to describe species responses by using several indicators. The study was carried out in the cities of Angers and Rennes (North-Western France) where 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…EIVs for soil N concentration and pH in the present study were similar to those reported for other swamp forests (Slezák et al, 2012). The studied species were indicators of weakly acid to weakly basic and indicated fertile soils with high bioactivity and alkaline and near neutral pH (Vallet et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…EIVs for soil N concentration and pH in the present study were similar to those reported for other swamp forests (Slezák et al, 2012). The studied species were indicators of weakly acid to weakly basic and indicated fertile soils with high bioactivity and alkaline and near neutral pH (Vallet et al, 2008).…”
Section: Discussionsupporting
confidence: 87%
“…By comparison, the conifer and oak species were more susceptible to human disturbances than the wind-disseminated species (Rudnicky and McDonnell 1989 ). In addition, and Vallet et al ( 2008 ) report a preponderance of nitrophilic species in remnant forest patches.…”
Section: Species Traitsmentioning
confidence: 95%
“…The edge effect on woodland plant communities is also expected to be particularly intense in urban areas, because the surrounding man-modified landscape matrix potentially leads to human disturbance (Matlack 1993b). In addition, urban plant communities are known to be especially rich in non-indigenous species (Deutschewitz et al 2003;Wania et al 2006) while both indigenous and nonindigenous species in urban areas differ in their ecological preferences from those found in rural areas (Godefroid and Koedam 2007;Thompson and McCarthy 2008;Vallet et al 2008). Species preferring fertile, dry, base-rich soils and unshaded habitats are known to be over-represented in urban plant communities (Knapp et al 2009;Thompson and McCarthy 2008).…”
Section: Introductionmentioning
confidence: 99%